PENGGUNAAN MEDIA PEMBELAJARAAN UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS III SDN ADIARSA BARAT IV PADA MATERI DAKWAN NABI MUHAMMAD SAW - Fanani, Dzulkifli Fahrul; Rahman, Rifqi Aulia; Amalia, Rosa; Puspitasari, Shela; ‘Atika, Risya; Khulasoh, Siti (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to develop a valid and practical mobile-based interactive learning media. The research method used is Research and Development (RD) by implementing the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The problem found in Informatics subject for class X TKJ at SMK Negeri 5 Padang indicates that practice-based learning has not been optimal, resulting in low student comprehension. Additionally, the use of information and communication technology in the learning process remains limited, and smartphones have not been fully utilized for learning purposes. The research results show that the validity level of the learning media assessed by media experts reached 91.05% with the category